Analyzing Isolates of Fusarium Head Blight in Wheat Across Kansas - Davis, Danielle; Dahal, Anusha; Bruce, Myron; Rupp, Jessica (My University, 2022)
One of the big threats to wheat farmers in Kansas is Fusarium Head Blight (FHB). This disease infects wheat heads, reducing the yield of the plant and releasing deoxynivalenol, a toxin that causes vomit sickness in humans and animals. This toxin is heavily regulated by the FDA making the sale of wheat seed infected with FHB nearly impossible and reducing the profit of that season. Preventing FHB in the field is difficult because wheat is only susceptible at heading, which makes the timing of fungicide application critical.. Research and communication between producers, breeders, and researchers attempt to find better ways of managing FHB. This project has collected samples of infected wheat heads from across Kansas from several different counties with the help of Kansas wheat breeders, Extension specialists, agents, ag industry professionals, and producers. Infected wheat heads are sterilized and the fungus is isolated. Fungal cultures underwent single-sporing to confirm a pure isolate. Then DNA is extracted and sequenced. This confirms that the fungus associated with the wheat head is Fusarium and what species. This process is done in hopes of different strains and a pattern in those differences across KS counties to develop more targeted methods of dealing with Fusarium Head Blight. This includes using these isolates in screening nurseries. This collaborative effort aims to help farmers respond more effectively to infection in the field and protect their crop and profit.
Keywords: plant pathology; Fusarium head blight; fungal isolation; single spore; DNA extraction; USDA NIFA 2019-67032-29071